Representasi Romantisme dalam Puisi “Aku Ingin” Karya Sapardi Djoko Damono - Fitria Ika Farizha; Dwi Wahyu Candra Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Literature as a medium to express ideas, emotions, or social problems that occur. This study aims to reveal the representation of romance in the poem "Aku Ingin" by Sapardi Djoko Damono by examining the use of figures of speech that contain romantic values. This poem is known as a work that is simple in structure but full of deep emotional meaning. Using a descriptive qualitative approach and content analysis method, this study analyzes the text of the poem to explore the elements of romance implied through diction, metaphors, and natural symbols. The results of the analysis show that Sapardi presents the concept of love that is calm, sincere, and does not demand explicit reciprocation. The representation of romance in this poem is seen in the simplicity of expressing feelings of love that emphasizes more on proof through actions and symbols rather than direct words. The use of metaphors in this poem strengthens the subtle romantic nuances, making love a form of devotion that is full of sincerity. The poem "Aku Ingin" reflects a unique dimension of romance that is different from classical romance, which is usually full of turmoil.